Mouse Models of Hepatocellular Carcinoma: Classification, Advancement, and Application - Liu, Sha; Huang, Fang; Ru, Guoqing; Wang, Yigang; Zhang, Bixiang; Chen, Xiaoping; Chu, Liang (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the highest incidence subtype of liver cancer, which is a heterogeneous malignancy with increasing incidence rate and high mortality. For ethical reasons, it is essential to validate medical clinical trials for HCC in the animal models before further consideration on humans. Therefore, appropriate models for study of the pathogenesis of the disease and related treatment methods are necessary. For tumor research, mouse models are the most commonly used and effective in vivo model, which is closer to the real life environment, and the repeated experiments performed on it are closer to the real situation. Several mice models of hepatocellular carcinoma have been developed with different mice strains, cell lines, tumor sites and tumor formation methods. In this review, we introduce some mouse HCC models, including induced model, gene-edited model, HCC transplantation model and other mice HCC models, and discuss how to choose the appropriate model according to the purpose of the experiments.